(untitled) (Research, Society and Development, 2021)
Objective: To describe the occurrence of self-reported Chronic Non-Communicable Diseases (NCDs) and related risk factors in nurses in the General and Pediatric Intensive Care Unit (ICU) in a reference hospital in the city of Maceió-AL. Methods: Descriptive study, carried out from April to July 2019. Data were obtained through a questionnaire prepared by the authors, with questions regarding personal and sociodemographic data, occupational and life habits and whether they already had such habits before the work in the ICU, in addition to self-reported anthropometric data. Results: 16 nurses were interviewed, 87.5% female, aged between 25 and 50 years, who worked in the sector between 11 and 15 years. Regarding the Body Mass Index, 37.5% were overweight and 6.25% were obese. 12.5% of the nurses declared they were smokers and 43.75% of the interviewees reported having acquired some NCDs during their professional performance in the ICU. Conclusion: The occurrence of identified NCDs and risk factors for its development was relatively high. The long working hours and the reduction in the quality of life of nursing professionals in the ICU proved to be important factors in common for the development of NCDs.